MEASURING THE PERFORMANCE IMPACT OF SERVITISATION :FROM INDIAN PORT PERSPECIVE - Chidambaram, Sree krishnan (2014)
This paper primarily focuses on measuring the performance impact and implementation of servitization in specific business relating to port in the sub-continent India . As servitization is a relatively new concept in the typical business world, this paper aims at contributing further more to the existing literature on the topic through referral of existing articles, books , other forms of literature and also involving real time companies and taking inputs from their business workings and interpreting them to further analysis . In today’s world the concept of servitisation is being implemented from an aeroplane engine to t-shirts. Service Providers and Manufactures have no longer relied on just plain product oriented sales or a pure service rendering firm but have mixed services and products along to entice and lure the customers attention towards their product .The paper is a conceptual analysis supported by empirical examples with relevance to today’s real world circumstances